Heavy metals tolerant native strains isolated from mining waste of the Hualilán mine, Argentina - Hidalgo, Natalia (2021)
Heavy-metal contamination is one of the most serious and complex environmental problems to be dealt with nowadays. Leaching piles from the mining industry are characterized by a high content of dissolved metals. In addition, they are considered to be a suitable habitat for the development of resistant microorganisms. Among such microorganisms are those native ones that are physiologically adapted to tolerate high concentrations of heavy metals and thus, are considered to be candidates for bioremediation processes. Taking this into consideration, the aim of this study was to isolate and select filamentous fungal strains with the potential to remove heavy metals. Samples of leaching piles were drawn from Hualilán Mine in the province of San Juan (Argentina). Isolation of filamentous fungi was carried out in a Sabouraud-glucose-agar medium with antibiotics, and the fungi were identified by using molecular biology techniques (amplification and sequencing of the fragment ADNr 18S y 26S, ITS1, ADNr 5.8S e ITS2). Tolerance to Cu (II) and Pb (II) was studied in plates with Potato dextrose agar (PDA) medium with concentrations between 25 and 800 ppm of each metal. Incubation conditions were at 28 °C during the period of total development of the fungi and compared with a control plate (without metal) by measuring growth diameters. A statistical analysis was carried out through variance analysis and Duncan means comparison test, with the ANOVA multifactor statistical software under a completely randomized experimental design with 2x6x1 factorial arrangement, a Petri dish as an experimental unit, and three repetitions. As a result, three strains were isolated, namely, Penicillium simplicissimum, Fusarium sp and Penicillium funiculosum. The fungi identified show tolerances to different concentrations of metal solutions, the most tolerant strain being Penicillium simplicissimum.